Impact of Satellite-Derived Diffuse Attenuation Coefficient on Upper Ocean Simulation Using High-Resolution Numerical Ocean Model: Case Study for the Bay of Bengal. Issue 6 (2nd November 2019) - Mallick, Subrat Kumar; Agarwal, Neeraj; Sharma, Rashmi; Prasad, K.V.S.R.; Weller, Robert A.
Abstract: Impact of satellite-derived shortwave attenuation depth and its spatial variability on the upper ocean dynamics has been studied using a numerical ocean model over the Bay of Bengal. We conducted two simulations, differing in the spatial distribution of shortwave attenuation depth for the period 2014–2015. The control run use a constant attenuation depth of 23 m (the default case for Type-I water) while the experimental run (ER) use spatially varying attenuation depths derived from daily climatology of the diffuse attenuation coefficient ( K d 490 ). Simulated parameters like sea surface temperature (SST) and mixed-layer depth (MLD) are sensitive to K d 490 that limits the penetration of downwelling shortwave radiation into the ocean. It has been found that K d 490 alters the upper ocean thermodynamics significantly. Validation has been performed using satellite, moored-buoy and profile data, for the year 2015. During spring, the errors in SST in the ER are reduced up to 35% at buoy location. The impact of improving shortwave attenuation depth is found to be maximum in the upper ocean (50–150 m). Error in simulated temperature at 100 m depth is reduced by 15% in the ER. MLD, barrier layer thickness, and the depth of 26 °C isotherm also show significant improvements in the ER.